Metformin Induces PRODH/POX-Dependent Apoptosis in Breast Cancer Cells - Huynh, Thi Yen Ly; Oscilowska, Ilona; Szoka, Lukasz; Piktel, Ewelina; Baszanowska, Weronika; Bielawska, Katarzyna; Bucki, Robert; Miltyk, Wojciech; Palka, Jerzy (Frontiers in Molecular Biosciences, 2022)
Although the antineoplastic activity of metformin (MET) is well established, the underlying mechanism of the activity is not understood. Since MET activates AMP kinase (AMPK) and proline dehydrogenase/proline oxidase (PRODH/POX) is stimulated by AMPK ligands (implicated in the regulation of cancer cell survival/apoptosis), the effect of MET on PRODH/POX-dependent apoptosis in wild-type MCF-7 cells (MCF-7WT) and POX knockdown MCF-7 cells (MCF-7crPOX cells) was studied. PRODH/POX catalyzes proline degradation generating ROS-induced apoptosis or autophagy. Availability of proline for PRODH/POX functions is regulated by the activity of prolidase (enzyme releasing proline from imidodipeptides), collagen biosynthesis (process consuming proline), and metabolism of proline, ornithine, and glutamic acid. We have found that MET is cytotoxic for MCF-7 cells (IC50∼17 mM), and to the lower extent for MCF-7crPOX cells (IC50∼28 mM). In MCF-7WT cells, the effect was accompanied by the inhibition of DNA biosynthesis, collagen biosynthesis, stimulation of ROS formation, AMPKα phosphorylation, and expression of prolidase, p53, caspase 8, caspase 9, and cleaved PARP. In MET-treated MCF-7crPOX cells, the processes were less affected than in MCF-7WT cells and the expression of caspase 9 was decreased, while cleaved caspase 8 and cleaved PARP were not detected. The effects were accompanied by an increase in the prolidase activity and proline concentration. The mechanism for MET-induced apoptosis involves the up-regulation of prolidase activity and a decrease in collagen biosynthesis contributing to an increase in the concentration of substrate (proline) for PRODH/POX-dependent ROS formation and activation of caspases −9 and −8. The data suggest that PRODH/POX participates in the MET-induced intrinsic and extrinsic apoptosis in MCF-7 cells.